The Effect of Armed Conflict on Biodiversity and its Implication on Wildlife: A Case Study on the Lebialem Highlands, South-West Region, Cameroon - Tabi, Enokenwa Allen; Younchahou, Mfonkwet Njiaghait; Mohanty, Abhijit (International Journal of Scientific Research in Biological Sciences, 2020)
The armed conflict in the Anglophone regions of Cameroon surged in 2016. In this conflict, many villages have been razed and hundreds of thousands of people displaced. In the South West Region, Lebialem is one of the hot zones of the conflict. Here, many displaced persons have found refuge in the forest; their impact on biodiversity cannot be undermined. The goal of this research paper is to highlight the impact of the armed conflict on the biodiversity and its implications for wildlife. In order to achieve this goal, the land cover of the study site was analyzed using satellite imagery. Two Landsat 8 OLI_TIRS satellite images taken in 2015 and 2020 were downloaded through the United States Geological Survey (USGS). These two images were processed using ENVI 5.3. Maps were produced by importing vectors derived from digital processing ENVI into Arc Map 10.5 software. A wildlife survey was conducted using the guided reconnaissance (recce) method. The results indicate that there was a slight change in dense forest cover of 0.26% (152 ha) and a general decrease in the relative abundance of Nigeria-Cameroon chimpanzee (from 2.964 in 2015 to 0.321 in 2018), Cross River gorilla (from 1.857 in 2015 to 0.107 in 2018), African forest elephants, and other species whose populations are vulnerable to human disturbance. Though armed conflict might have its own impacts on biodiversity and wildlife species, a strong conservation program is needed for the development of local professionals to continue even during socio-political instability.